Rattling in the Quadruple Perovskite CuCu3V4O12. Issue 37 (23rd July 2015) - Akizuki, Yasuhide; Yamada, Ikuya; Fujita, Koji; Taga, Kazuya; Kawakami, Takateru; Mizumaki, Masaichiro; Tanaka, Katsuhisa
Abstract Of particular interest is a peculiar motion of guest atoms or ions confined to nanospace in cage compounds, called rattling. While rattling provides unexplored physical properties through the guest–host interactions, it has only been observed in a very limited class of materials. Herein, we introduce an A‐site‐ordered quadruple perovskite, CuCu3V4O12, as a new family of cage compounds. This novel AA′3B4O12‐type perovskite has been obtained by a high‐pressure synthesis technique and structurally characterized to have cubic Im<alternatives> <![CDATA[$\bar 3$]]> <inline-graphic xlink:href="ark:/27927/pgj2h31jn3w" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives> symmetry with an ionic model of Cu2+Cu2+3V4+4O12. The thermal displacement parameter of the A‐site Cu2+ ion is as large as Uiso≈0.045 Å2 at 300 K, indicating its large‐amplitude thermal oscillations in the oversized icosahedral cages. Remarkably, the presence of localized phonon modes associated with rattling of the A‐site Cu2+ ion manifests itself in the low‐temperature specific heat data. This work sheds new light on the structure–property relations in perovskites.